Apple nucleobase cation symporter 1 transports guanine and the toxic guanine analog 6-thioguanine. (August 2020) - Iman, Adrita; Huntley, Regan B.; Mourad, George S.; Schultes, Neil P.
Abstract: Erwinia amylovora causes fire blight, a devastating disease of apples and pears . The antimetabolite 6-thioguanine (6 TG) is synthesized and excreted by this bacterium and is involved in pathogenesis. Plants contain numerous nucleobase transporters that readily transport guanine. Studies of the Malus domestica nucleobase cation symporter 1 (MdNCS1) by heterologous expression in nucleobase transport deficient Escherichia coli, reveals transport of adenine, guanine and 6 TG. This is the first report of a plant transporter moving 6-thioguanine, a toxic nucleobase derivative produced by the apple pathogen Erwinia amylovora. MdNCS1 is expressed in both uninfected and E. amylovora infected apple flowers (a common route for pathogen entry) and in E. amylovora infected immature pear fruitlets. Highlights: Erwinia amylovora causes fire blight. E. amylovora makes toxic 6-thioguanine. Apple nucleobase cation symporter 1 moves 6-thioguanine.